Composite adsorbent material for the effective removal of benzaldehyde from Chinese spirit: synergistic adsorption behavior of AC-SiO2 - Xiuzhen Xu; Zhicheng Jiang; Shuguang Xu; Bi Shi (Biochar)
Abstract The efficient conversion of distiller’s grains (DGs) into high-value products will promote the sustainable development of the Chinese spirit industry and reduce related environmental issues. Herein, a composite adsorbent material (AC-SiO2) composed of activated carbon (AC) and silica (SiO2) was prepared from DGs via sequential pyrolysis, KOH etching, and steam activation processes. AC-SiO2 was used to remove benzaldehyde from the Chinese spirit to improve the aroma and quality of the spirit. The experiment results showed that, KOH etching effectively removed SiO2 from DGs and exposing the carbon substrate for further steam activation, then the specific surface area of AC-SiO2 extremely increased to 1213.0 m2 g–1. Steam activation introduced Si–OH/Si–H bonds on SiO2 and –OH/–COOH groups on the carbon surface and increased the graphitization degree of the materials. After optimization of the AC-SiO2 preparation processes, the obtained AC-SiO2 removed 68.7% of benzaldehyde from the spirit. The high benzaldehyde removal rate of AC-SiO2 was attributed to the synergistic effect of AC and SiO2 components (binding energy up to − 15.45 kcal mol–1), where benzaldehyde was preferentially adsorbed on the AC-SiO2 interface. Specifically, highly graphitized AC promoted the planar adsorption of the benzene ring in benzaldehyde via π-π stacking, and the Si–OH/Si–H bonds on SiO2 adsorbed the aldehyde group of benzaldehyde via hydrogen bonding. This study not only presents a novel approach to DGs resource utilization, but also provides theoretical underpinnings and technical support for the spirit quality enhancement, significantly promoting the green and sustainable development of the spirit industry. Graphic Abstract